Comparison of Antioxidant Power Extract of Ethanol Extract, Hard Shell and Seeds on Melinjo ( Gnetum gnemon L.) with DPPH Method (1,1-diphenyl-2-picrylhydrazyl) - Windy Widyawatin; Marlina Indriastuti (Ad-Dawaa : Journal of Pharmacy, 2023)
The human body cannot be avoided from exposure to free radicals in everyday life. Free radicals are very dangerous for the body, one of which causes degenerative diseases. One of the plants that is thought to be able to inhibit free radicals is the melinjo plant. The processing of melinjo plants in the community is only used as a vegetable, so there is a need for research on the benefits of antioxidants in melinjo plants. The purpose of this study was to explore the parts of melinjo which had the best antioxidant activity found in the soft shell, hard shell and seeds of melinjo (Gnetum gnemon L.) with different solvent concentrations. The research method used was to prepare test samples by maceration process using 50% and 70% ethanol, then the extracts were tested for antioxidants using the DPPH method. Data analysis was performed using the ANOVA statistical test with a 98% confidence level. The results showed that the optimal percentage of free radical inhibition was obtained in 50% ethanol solvent, the outer shell of melinjo was 53.29%, and the IC50 was 318.18 ppm. Based on the One way Anova test (p>0.02) there was no difference between the use of 50% and 70% ethanol solvent on the antioxidant activity of the outer shell, hard skin and melinjo seed samples.